Kritik HadÃ®th dalam Perspektif Studi Kontemporer - Idri, Idri (Program Pascasarjana UIN Sunan Ampel Surabaya, 2010)
Critical studies of hadÃ®th do not always aim at arguing against the legitimacy of hadÃ®th as one of the sources of Islamic Law. Nor do it doubt âlike many orientalist would do- the authenticity of the hadÃ®th as a source of Islamic teaching. Critical studies of hadÃ®th are about investigating the accuracy and validity of the narration chain. Considering that many hadÃ®ths take a long period of time before they are being narrated, inaccuracy might have taken place in that process. Therefore a critique is needed. In the context of contemporary life, a critique is even more needed especially that which looks at hadÃ®th in terms of its relation with modern science, technology, gender issues, human rights, freedom of expression, and so on. This paper discusses the notion of the critical studies of hadÃ®th in contemporary life by focusing on four issues (1) the cognitive foundation of the studies, (2) the objects of the critique, (3) the necessity of the critique, and (4) the normative standards of the critique.